2002
DOI: 10.1177/15648265020233s140
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Iron Fortificants on Iron Absorption from Iron-Fortified Rice

Abstract: Iron absorption from rice fortified with different iron fortificants, e.g., ferrous sulfate (FeS0 4), sodium iron EDTA (NaFeEDTA), ferrous fumarate (FeFum), and ferrous bisglycinate (FeBis) was determined using an in vitro enzymatic digestion method simulating conditions in the small intestine and an in vivo method using radioisotope techniques. The in vitro method showed that the percentage of dialyzable iron from NaFeEDTA (15.7 ± 0.9) and FeS0 4-fortified rice (13.2 ± 1.5) was significantly greater than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…In cereal that has a high phytate concentration, the bioavailability of iron from NaFeEDTA is two to three times higher than that of iron from ferrous sulfate [26]. Trinidad et al [27] investigated the bioavailability of iron from ferrous sulfate and NaFeEDTA in fortified rice by both in vitro and in vivo methods. The in vivo study showed that the percentage of iron absorption from NaFeEDTA was higher than that from ferrous sulfate, whereas no difference was found by the in vitro method.…”
Section: Dialyzability Of Iron From Various Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In cereal that has a high phytate concentration, the bioavailability of iron from NaFeEDTA is two to three times higher than that of iron from ferrous sulfate [26]. Trinidad et al [27] investigated the bioavailability of iron from ferrous sulfate and NaFeEDTA in fortified rice by both in vitro and in vivo methods. The in vivo study showed that the percentage of iron absorption from NaFeEDTA was higher than that from ferrous sulfate, whereas no difference was found by the in vitro method.…”
Section: Dialyzability Of Iron From Various Sourcesmentioning
confidence: 99%
“…Color and water activity of dried rice and color and pH of cooked broken rice fortified with different calcium and iron fortificants a 27 . 2.91 ± 0.08 13.68 ± 0.27 70.41 ± 0.10 -5.18 ± 0.14 5.00 ± 0.03 5.25 ± 0.02 0.22 ± 0.03 CLG + NaFeEDTA 88.29 ± 0.61 -0.32 ± 0.12 11.44 ± 0.22 71.00 ± 0.62 -4.3 ± 1.33 3.17 ± 3.23 5.69 ± 0.02 0.26 ± 0.13 CLG + Fe lactate 90.73 ± 0.60 -2.98 ± 0.03 13.85 ± 0.50 72.93 ± 0.57 -3.56 ± 0.57 2.21 ± 3.54 5.33 ± 0.03 0.18 ± 0.05 CL+ FeSO 4 87.77 ± 0.51 -1.53 ± 0.12 14.86 ± 0.08 72.65 ± 0.86 -4.45 ± 0.79 6.72 ± 0.82 5.24 ± 0.01 0.20 ± 0.05 CL+ NaFeEDTA 87.82 ± 0.41 -0.22 ± 0.29 10.56 ± 0.46 71.20 ± 0.37 -3.11 ± 0.49 7.47 ± 0.10 5.72 ± 0.03 0.17 ± 0.02 CL+ Fe lactate 88.40 ± 01.20 -1.45 ± 0.11 14.03 ± 0.06 70.83 ± 1.13 -2.91 ± 0.37 6.99 ± 0.67 5.22 ± 0.03 0.21 ± 0.05…”
mentioning
confidence: 99%
“…FeAAC has been used to fortify sweet rolls, cheese and milk for consumption by young children and substantial improvements in iron status indicators (serum levels of haemoglobin and ferritin, TIBC, ferritin) were reported 38–41. On the other hand, other studies have shown that FeAAC, compared to other iron fortificants, was less effective on iron absorption when using iron‐fortified rice 42. However, to the authors' knowledge, there are no previous studies on the absorption and iron status of FeAAC when added to an infant formula.…”
Section: Discussionmentioning
confidence: 99%
“…Mean iron absorption from ferrous fumarate was similar to that from ferrous sulfate (absorption ratio 0.91‐1.28). A recent study by Trinidad et al (13) found that percentage of dialyzable iron from NaFeEDTA (15.7‐0.9) and ferrous sulfate (13.2‐1.5) was significantly greater than that from ferrous fumarate (6.0‐0.6). This agrees with the findings of the study under discussion.…”
mentioning
confidence: 98%